2002
DOI: 10.1002/ajmg.10906
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal risk factors for schizophrenia: Diagnostic specificity and relationships with maternal psychopathology

Abstract: Although a growing body of evidence supports the hypothesis that exposure to obstetric complications (OCs) increases the vulnerability for schizophrenia, some questions remain unanswered regarding the diagnostic specificity and the etiological significance of this association. Associations with a history of OCs have been reported for other severe psychiatric disorders, such as autism, anorexia nervosa, or psychotic affective disorder. Thus, OCs may increase in a relatively non-specific way the vulnerability fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 66 publications
1
22
0
2
Order By: Relevance
“…7 The literature shows that poor fetal development, in terms of weight and length, is associated with low adult height, 7,8 early menarche age, 9 and an increased risk of several psychiatric and nonpsychiatric diseases. [10][11][12] Few studies to date have explored the relationship between height and eating disorders. [13][14][15][16] These studies usually deal with small samples of early-onset anorexia nervosa cases and show the presence of a growth retardation usually-but not always 13 -attributed to malnutrition and endocrinological alterations.…”
Section: Introductionmentioning
confidence: 98%
“…7 The literature shows that poor fetal development, in terms of weight and length, is associated with low adult height, 7,8 early menarche age, 9 and an increased risk of several psychiatric and nonpsychiatric diseases. [10][11][12] Few studies to date have explored the relationship between height and eating disorders. [13][14][15][16] These studies usually deal with small samples of early-onset anorexia nervosa cases and show the presence of a growth retardation usually-but not always 13 -attributed to malnutrition and endocrinological alterations.…”
Section: Introductionmentioning
confidence: 98%
“…Schizophrenia studies implicate, however, that environmental factors are not simply a causal continuum of genetic factors. Compared to siblings, normal controls and psychiatric controls, schizophrenic inpatients seem to be more likely to have experienced perinatal obstetric complications [42]. Studies in bipolar disorder also support this view because they have found a significant excess of obstetrical complications among bipolar inpatients compared with their own biological siblings [29].…”
Section: Discussionmentioning
confidence: 59%
“…Epidemiological (Cannon et al 2002;Verdoux and Sutter 2002) and experimental animal studies (Rees and Inder 2005;Boksa 2004;Boksa and El-Khodor 2003) suggest an association between a variety of obstetric complications and an increased risk for schizophrenia and support the neurodevelopmental hypothesis of the disorder (Cannon et al 2002). The obstetric complications include maternal viral infections, starvation, or malnutrition, stress, premature, or early birth (low birth weight and/or short gestational age; Verdoux and Sutter 2002).…”
Section: Introductionmentioning
confidence: 95%